Pengawetan Sari Buah Mangga Arum Manis (Mangifera Indica L) Menggunakan Eugenol - Ery Fatarina Purwaningtyas; Wafik Nur Maulina; Sri Mulyaningsih (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
Sweet arum mango is one type of mango which when harvested has the highest vitamin C content of 7.53 ± 0.4 mg / 100 g. Processed sweet arum mango fruit products that have the potential to be developed are in the form of fruit juice. This is a consideration for researchers to conduct further research on the addition of eugenol preservatives with different concentrations of preservatives and storage times to produce better mango juice. Eugenol compounds have pharmacological activities as analgesics, anti-inflammatory, antimicrobial, antifungal, antiseptic, stimulant, so these compounds are widely used in the pharmaceutical industry. Based on the experimental results, optimal conditions for the use of eugenol occurred until day 2, where the addition of eugenol with treatment 3 as much as 1 ml amounted to 38.82% better when compared to other variations of eugenol addition. The addition of eugenol preservatives cannot preserve the content of vitamin C in sweet mango juice even the content of vitamin C tends to decrease. Sweet arum mango juice has a shelf life of 12 days and total dissolved solids of more than 20%, so the resulting fruit juice does not meet SNI 7382:2009.